Syntactic Analysis of the Noun Phrases in Justin Bieber’s Song Lyrics - Nasution, Andini nabila; Setia, Eddy; Deliana, Deliana (Politeknik Harapan Bangsa Surakarta, 2024)
This thesis showed the syntactic analysis of the noun phrases used in Justin Bieber’s song lyrics. The objectives of the study are: (1) to find out the noun phrases in Justin’s selected song lyrics. (2) to find out the most dominant noun phrases among Justin’s selected song lyrics. It was a qualitative descriptive research with Labelled Bracketing by Lesley Milroy as its approaches. The writer used 3 data of song lyrics then classified, analyzed and counted the data. The result of this study showed that there were 50 noun phrases with the details as follows : 15 noun phrases in What Do You Mean song lyrics (30%), 16 noun phrases in Sorry song lyrics (32%) and 19 noun phrases in Love Yourself song lyrics (38%). And the most dominant noun phrases found in Love Yourself song lyrics with 38% (19 noun phrases).